State Machine Replication for the Masses with BFT-SMaRt - Sousa, João (2013)
The last fifteen years has seen an impressive amount of work on protocols for Byzantine fault-tolerant (BFT) state machine replication. However, there is still a lack of practical and reliable software libraries implementing this technique. BFT-SMaRt is an open-source Java-based library implementing robust BFT state machine replication. Some of the key features of this library that distinguishes it from similar works (e.g., PBFT and UpRight) are improved reliability, modularity as a first-class property, multicore-awareness, reconfiguration support and an flexible API. When compared with other SMR libraries, BFT-SMaRt achieves better performance and is able to deal with a number of real-world faults previous implementations can not.